Welcome to the hotseat. We've prepared a guide if you'd like to read more about how it works.

for question 9.8 in DHW: how do we know or prove that for independent lives that u_x+t:y+t = U_x+t + U_y+t

0 votes
asked Nov 15, 2017 in BUS 3024S - Contingencies by adam (160 points)

The question ask to show that the density of T_xy is tpxy(ux+t+uy+t)

1 Answer

0 votes
answered Nov 21, 2017 by Feroz (1,350 points)

First, we find the distribution function of \(T_{xy}\):

$$Pr(T_{xy} \leq t) = 1 - Pr(T_{xy} > t) = 1 - Pr(T_{x} > t) \cdot Pr(T_{y} > t) = 1 - {}_t p_{x} {}_t p_{y}$$.

To find the density, we differentiate the above expression with respect to \(t\). 

$$f_{T_{xy}}(t) = \frac{d}{dt} Pr(T_{xy} \leq t) = {}_t p_{xy}(\mu_{x+t}+ \mu_{y+t})$$ (you need to use the product rule to differentiate the second term in the expression for \(Pr(T_{xy} \leq t) \)).

You will also need expressions of the following form:

$$\frac{d}{dt} {}_t p_{x} = -{}_t p_{x} \mu_{x+t}$$.

Hope this helps.